Conceptual, methodological, and measurement factors that disqualify use of measurement invariance techniques to detect informant discrepancies in youth mental health assessments - De Los Reyes, Andres; Tyrell, Fanita A.; Watts, Ashley L.; Asmundson, Gordon J. G. (Frontiers in Psychology, 2022)
On page 1 of his classic text, Millsap (2011) states, “Measurement invariance is built on the notion that a measuring device should function the same way across varied conditions, so long as those varied conditions are irrelevant to the attribute being measured.” By construction, measurement invariance techniques require not only detecting varied conditions, but also ruling out that these conditions inform our understanding of measured domains (i.e., conditions that do not contain domain-relevant information). In fact, measurement invariance techniques possess great utility when theory and research inform their application to specific, varied conditions (e.g., cultural/ethnic/racial background of test respondents) that, if not detected, introduce measurement biases and thus depress measurement validity (e.g., academic achievement, intelligence). Yet, we see emerging bodies of work where scholars have “put the cart before the horse” when it comes to measurement invariance, and they apply these techniques to varied conditions that, in fact, may reflect domain-relevant information. These bodies of work highlight a larger problem in measurement that likely cuts across many areas of scholarship. In one such area, youth mental health, researchers commonly encounter a set of conditions that nullify the use of measurement invariance, namely discrepancies between survey reports completed by multiple informants such as parents, teachers, and youth themselves (i.e., informant discrepancies). In this paper, we provide an overview of conceptual, methodological, and measurement factors that should prevent researchers from applying measurement invariance techniques to detect informant discrepancies. Along the way, we cite evidence from the last 15 years indicating that informant discrepancies reflect domain-relevant information. We also apply this evidence to recent uses of measurement invariance techniques in youth mental health. Based on prior evidence, we highlight the implications of applying these techniques to multi-informant data, when the informant discrepancies observed within these data might contain domain-relevant information. We close by calling for a moratorium on applying measurement invariance techniques to detect informant discrepancies in youth mental health assessments. In doing so, we describe how the state of the science would need to fundamentally “flip” to justify applying measurement invariance techniques to detect informant discrepancies in multi-informant data.